Environmental Problems of Chewing Chrome Tanned Leather - Niyazova Rano Nazhmutdinovna (Zien Journals, 2022)
The basic principles (approaches) of composing fat compositions have been developed, based on the purpose of the skin, based on the establishment of a relationship between the colloid-chemical characteristics of the initial living materials and the properties of the skin.
Keywords: Certification of Products; Effluents and Waste; Nature of Living Materials